Personalizm ekonomiczny i jego zasady w ujęciu G.M.A. Gronbachera - Urgacz, Paweł (Annales. Etyka w Życiu Gospodarczym, 2008)
The dialog that has been conducted for a few years between a group of Christian social thinkers and economists on moral aspects of economic activity has led to the creation of a new science discipline called economic personalism. On the one hand it stipulates the need to express economic processes within ethical categories, on the other hand it perceives the necessity to elaborate a strong economic theory. Economic personalists refer to the works of those thinkers who returned to the basic economic inspiration as a field belonging predominantly to moral philosophy. This school is sometimes called the Austrian School or the School of Classical Liberalism. A significant role in the economic personalism development was performed by its forerunners who noticed what was lacking in the previous interpretations of Catholic social thought. Among the there are John Paul II, Michael Novak, Rocco Buttiglione and the Acton Institute. The intellectual sources of economic personalism are mainly related to concept of personalism developed in Poland. Its specific thesis, seen in the maxim that “each person ought to be affirmed for the sake of it itself” also relates to the economic life. Economic personalists formulate principles that are spokesmen in order to promote a free society built on virtues. They are expressed in the following way: pre-eminence of a human being: economy and human dignity; human capital: creation and creativity; dignity of human work: calling for enterprise, integral development of human being, manufacture and personalism, participation, economic common wealth, helpfulness, market restrictions; preferential option for the poor: solidarity and social equity.